2007
DOI: 10.1242/jcs.014365
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian diaphanous-related formin Dia1 controls the organization of E-cadherin-mediated cell-cell junctions

Abstract: The formin-homology protein Dia1 is a target of RhoA and a potent activator of nucleation and elongation of actin filaments. Here, we demonstrate that short-hairpin (sh) RNA-mediated downregulation of Dia1 in human MCF7 epithelial cells disrupts adherens junctions, as manifested by the significantly decreased localization of E-cadherin and associated proteins to cell-cell contacts. Expression of mouse Dia1, which is insensitive to the human Dia1-specific shRNA, rescued the junctional integrity. Coexpression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
130
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 74 publications
14
130
1
1
Order By: Relevance
“…In particular, formin activity, which polymerizes long, parallel actin bundles found in filopodia (46, 47), appeared to be essential for cell adhesion and dynamic filopodialike protrusions on a 30-kPa Ecad-Fc PA gel, but not on a 60-kPa Ecad-Fc PA gel. These results are consistent with previous studies that demonstrated a role for the diaphanous formin mDia1 (11,65,66) and formin-like proteins FMNL2 and FMNL3 (12,13) in the recruitment of actin and E-cadherin and the formation of filopodia at initial cell-cell contacts. At present, we do not know which formin(s) is (are) regulated by the stiffness of E-cadherin interactions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In particular, formin activity, which polymerizes long, parallel actin bundles found in filopodia (46, 47), appeared to be essential for cell adhesion and dynamic filopodialike protrusions on a 30-kPa Ecad-Fc PA gel, but not on a 60-kPa Ecad-Fc PA gel. These results are consistent with previous studies that demonstrated a role for the diaphanous formin mDia1 (11,65,66) and formin-like proteins FMNL2 and FMNL3 (12,13) in the recruitment of actin and E-cadherin and the formation of filopodia at initial cell-cell contacts. At present, we do not know which formin(s) is (are) regulated by the stiffness of E-cadherin interactions.…”
Section: Discussionsupporting
confidence: 93%
“…Adhesion is initiated when filopodia from opposing cells come into contact with one another (7,8), and this process is regulated by Cdc42 activity (9, 10) and formin-dependent actin polymerization (11)(12)(13)(14). Intermediate stages of cell-cell contact formation involve lateral expansion of the contact by Rac1-induced and Arp2/3-dependent lamellipodial activity (15, 16).…”
mentioning
confidence: 99%
“…Dia1, a RhoA effector that is proposed to regulate cell junction stability (27,28), belongs to the formin family and can remodel the actin cytoskeleton (29). We previously identified Dia1 as the key downstream effector of Syx in regulating junction integrity (5).…”
Section: Discussionmentioning
confidence: 99%
“…16,29 In epithelial cells, expression of Dia1 reinforces the adhesion zone, whereas Dia1 knockdown results in decreased junctional E-cadherin. 30 Formin-1, a Dia1 related protein, is required at the intercellular junctions to direct actin cable formation and to support cell-cell contact in mouse keratinocytes in vivo. 31 Furthermore, Dia1 knockout mice exhibit severe defects in neuroepithelial junction formation and polarization, supporting its indispensable role in regulating cell-cell adhesion and monolayer integrity.…”
Section: Dia and Rock: Friends Or Foes?mentioning
confidence: 99%
“…Dia1 is proposed to have a housekeeping function in stabilizing cell junctions. 30 Even though the mechanism of Dia1 recruitment to cell-cell contacts is unclear, its basal activity is likely maintained by upstream RhoA signaling at the junctions. ROCK binds several junctional proteins such as p120, Shroom 3, and p114RhoGEF, 43,50,51 suggesting that its recruitment to the cell membrane is highly regulated and that its activation is dependent on its immediate associated protein complex.…”
Section: Working In Synergy: Selective and Balanced Signaling By Dia mentioning
confidence: 99%